SPINAL TRACTION - Saime Sarıoğlu,; Gülay Dinçer, (Archives of Rheumatology, 2003)
Spinal traction is a technique using a force or a system of force to seperate joint face and bone fragmants, and to stretch and elongate the soft tissue. Spinal traction is most commonly used in cervical and lomber regions. Thoracic, sacral and pelvic tractions are also used but with little effect. Traction can be continuous, sustained and intermittent. Traction is obtained by using a force with an optimal position, amount and duration. The correct position of the patient and the correct angle of the pull, the traction can be localised to a certain spinal area. The purpose of traction is to decrease pain and improve function.